An extra virgin olive oil‐enriched diet improves maternal, placental, and cord blood parameters in GDM pregnancies. Issue 8 (24th June 2020) - Gomez Ribot, Dalmiro; Diaz, Esteban; Fazio, María Victoria; Gómez, Hebe Lorena; Fornes, Daiana; Macchi, Silvia Beatriz; Gresta, Carlos Alberto; Capobianco, Evangelina; Jawerbaum, Alicia
Abstract: Aims: To address the effect of a diet enriched in extra virgin olive oil (EVOO) on maternal metabolic parameters and placental proinflammatory markers in Gestational diabetes mellitus (GDM) patients. Methods: Pregnant women at 24‐28 weeks of gestation were enrolled: 33 GDM patients which were randomly assigned or not to the EVOO‐enriched group and 17 healthy controls. Metabolic parameters were determined. Peroxisome proliferator activated receptor (PPAR) γ and PPARα protein expression, expression of microRNA (miR)‐130a and miR‐518d (which respectively target these PPAR isoforms) and levels of proinflammatory markers were evaluated in term placentas. Matrix metalloproteinases (MMPs) activity was evaluated in term placentas and umbilical cord blood. Results: GDM patients that received the EVOO‐enriched diet showed reduced pregnancy weight gain (GDM‐EVOO:10.3 ± 0.9, GDM:14.2 ± 1.4, P = .03) and reduced triglyceridemia (GDM‐EVOO:231 ± 14, GDM:292 ± 21, P = .02) compared to the non‐EVOO‐enriched GDM group. In GDM placentas, the EVOO‐enriched diet did not regulate PPARγ protein expression or miR‐130a expression, but prevented the reduced PPARα protein expression ( P = .02 vs GDM) and the increased miR‐518d expression ( P = .009 vs GDM). Increased proinflammatory markers (interleukin‐1β, tumour necrosis factor‐α and nitric oxide overproduction) in GDM placentas were prevented by the EVOO‐enriched diet (respectively P = .001, P = .001 and P = .01 vs GDM). MMPs overactivity was prevented in placenta and umbilical cord blood in the EVOO‐enriched GDM group (MMP‐9: respectively P = .01 and P = .001 vs GDM). Conclusions: A diet enriched in EVOO in GDM patients reduced maternal triglyceridemia and weight gain and has antiinflammatory properties in placenta and umbilical cord blood, possibly mediated by the regulation of PPAR pathways.